"Family Comes First!" Relationships with family and friends in Italian emerging adults. Issue 8 (18th March 2014) - Crocetti, Elisabetta; Meeus, Wim
ABSTRACT: We conducted two studies to examine relationships with family and friends in Italian emerging adults, paying attention to the potential moderating role of gender and occupational status. In Study I, we aimed at capturing emerging adults' perspective on interactions with both family and friends by means of a qualitative approach. Participants were 39 emerging adults (51% males), who were interviewed individually or within a focus group. In Study II, we sought to examine how family and friend importance to identity were related to life satisfaction through a quantitative approach. Participants were 474 (47.3% males) emerging adults who filled a self‐report questionnaire. Overall, findings indicated solid family ties and a strong impact of family importance to identity for life satisfaction. Results were independent of gender and occupational status (university students vs. workers). Thus, findings highlighted that in the Italian context young people's transition to adulthood is strongly intertwined with family relationships.